PRODUCTION AND UTILIZATION OF CELLULASE FROM TRICHODERMA VIRIDE - SURYAHADI SURYAHADI; R. HIDAYAT; S. WULANDARI; K.G. WIRYAWAN (BIOTROPIA, 2005)
Â  An appropriate preservation technology for forage such as silage needs to be developed in order to overcome the shortage of tropical forage during the dry season. A good quality of silage is obtained by decreasing the fibre contents (Neutral Detergent Fibre, Acid Detergent Fibre and lignin). The research was conducted in two stages: 1). Production and activity test of crude enzymes from Trichoderma viride and 2). Comparative test using crude enzymes fromÂ  Trichoderma viride strain QM 9414 (CETV) and commercial cellulase (Cellulase â€œOnozuka R-10â€, heidelberg) on rice straw silage. The treatments were arranged as follows : P0=Untreated rice straw silage, P1=Treated with commercial cellulase at 10 IU kg-1, P2= Treated with CETV at 3.8 IU kg-1, P3=Treated with CETV at 7.6 IU kg-1Â  and P4= Treated with CETV at 11.4 IU kg-1Â of fresh rice straw. All treatments were enriched with 5% molasses. The result of the research indicated that: 1). The activity of crude enzymes from Trichoderma viride strain QM 9414 (CETV) was 1.52 IUml-1. 2). The addition of both enzymes did not decrease dry matter of rice straw silage; however, organic matter significantly decreased (p